IMPLIKASI POLITIK HUKUM KEIMIGRASIAN INDONESIA DALAM PEMBATASAN PERLINTASAN TERHADAP PEMULIHAN EKONOMI PASCA KEADAAN DARURAT COVID-19 - Ika Wahyuni; Mahmul Siregar; Detania Sukarja; Mirza Nasution (Journal Publicuho, 2025)
This research analyses the legal politics of Indonesia's immigration policy during and after the COVID-19 pandemic in the context of national economic recovery. By employing a normative juridical method with a conceptual and statutory approach, the study explores how legal instruments such as visa restrictions and movement control served as tools to protect national security and public health, while also impacting state revenue from the non-tax sector. The results show that post-pandemic immigration policy was strategically adapted to optimise economic functions, such as through the implementation of selective visa policies and innovations like the "Eazy Passport" service. These efforts contributed significantly to the recovery of tourism and the increase of non-tax state revenue (PNBP). The study concludes that immigration policy has effectively transformed from a regulatory mechanism into an economic stimulus instrument, and recommends that future immigration policy remain adaptive and balanced between economic benefit and national security.